Synthesis, Molecular Docking and Mosquitocidal Efficacy of Lawsone and its Derivatives Against the Dengue Vector Aedes aegypti L. (Diptera: Culicidae) - Stalin, Antony; Dhivya, Paul; Lin, Ding; Feng, Yue; Asharaja, Antony C.; Gandhi, Munusamy Rajiv; Kannan, Balakrishnan Senthamarai; Kandhasamy, Subramani; Reegan, Appadurai Daniel; Chen, Yuan (Medicinal Chemistry, 2022)
Background: Aedes aegypti is the primary vector of dengue, a significant public health problem in many countries. Controlling of Ae. aegypti is the biggest challenge in the mosquito control programe, and there is a need for finding bioactive molecules to control Ae. aegypti in order to prevent dengue virus transmission. Objective: To assess the mosquitocidal property of lawsone and its 3-methyl-4H-chromen-3-yl-1- phenylbenzo[6,7]chromeno[2,3,c]pyrazole-dione derivatives (6a-6h) against various life stages of Ae. aegypti. Besides, to study the mode of action of the active compound by molecular docking and histopathological analysis. Methods: All derivatives were synthesized from the reaction between 2-hydroxy-1,4-naphthoquinone, chromene-3-carbaldehyde, and 1-phenyl-3-methyl-pyrazol-5-one by using one pot sequential multicomponent reaction. The mosquito life stages were subjected to diverse concentrations ranging from 1.25, 2.5, 5.0, and 10 ppm for lawsone and its derivatives. The structure of all synthesized compounds was characterized by spectroscopic analysis. Docking analysis was performed using autodock tools. Midgut sections of Ae. aegypti larvae were analyzed for histopathological effects. Results: Among the nine compounds screened, derivative 6e showed the highest mortality on Ae. aegypti life stages. The analyzed LC<50 and LC90 results of derivative 6e were 3.01, 5.87 ppm, and 3.41, 6.28 ppm on larvae and pupae of Ae. aegypti, respectively. In the ovicidal assay, the derivative 6e recorded 47.2% egg mortality after 96-hour post-exposure to 10 ppm concentration. In molecular docking analysis, the derivative 6e confirmed strong binding interaction (-9.09 kcal/mol and -10.17 kcal/mol) with VAL 60 and HIS 62 of acetylcholinesterase 1 (AChE1) model and LYS 255, LYS 263 of kynurenine aminotransferase of Ae. aegypti, respectively. The histopathological results showed that the derivative 6e affected the columnar epithelial cells (CC) and peritrophic membrane (pM). Conclusion: The derivative 6e is highly effective in the life stages of Ae. aegypti mosquito and it could be used in the integrated mosquito management programe.
Keywords: Multi-Component Reaction